2013
DOI: 10.1177/1474515113478531
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient-held alert cards in promoting continuity of care for Heart Failure Patients

Abstract: The study has shown that alert cards can increase the involvement of CHFSNs in the ongoing care and discharge planning process. They can also empower patients and carers to take an active role in their own care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…As such, we suggest the use of an alert card, whereby the patient's renal function can be recorded and made available in the outpatient and community settings. A pilot study on patient‐held alert cards for heart failure patients in the UK showed that alert cards could help improve continuity of care, increase community–hospital contact and empower patients . A recent study performed in Malaysia showed that the Malaysian population has poor knowledge of CKD, particularly those who have risk factors and those with a lower socioeconomic status .…”
Section: Discussionmentioning
confidence: 99%
“…As such, we suggest the use of an alert card, whereby the patient's renal function can be recorded and made available in the outpatient and community settings. A pilot study on patient‐held alert cards for heart failure patients in the UK showed that alert cards could help improve continuity of care, increase community–hospital contact and empower patients . A recent study performed in Malaysia showed that the Malaysian population has poor knowledge of CKD, particularly those who have risk factors and those with a lower socioeconomic status .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the mental health and intellectual disabilities field shows that self-empowerment, advocacy, and communication tools can improve care. Self-advocacy research to support communication in ED care for children and heart-failure patients suggests that empowerment approaches can inform a better way to provide hospital and ED services (Feldman et al., 2012; Hoppa & Porter, 2011; McBride, Burey, Megahed, Feldman, & Deaton, 2014; Picket et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all programmes provided written education to the patients and to some extent to their families, the rest of the centres provided written education to the patients. And there seems a continuous interest to improve educational and self-care material [ 15 , 16 ].The components rated as most important by the health care professionals are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%